The Law and Tradition of Weton Calculation in the Javanese Community of Jombang East Java (Study in Balong Besuk Village, Diwek Jombang) - Ma'ruf, M; Kusumawati, Ita Rahmania (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2023)
This study aims to determine the paradigm of weton calculation in marriage in Balong Besuk Village, Diwek District, Jombang Regency. In addition, it is also to find out what factors cause the calculation of weton in the community. This research includes field research using qualitative methods. The data collection uses interview, observation, and documentation methods. The data sources consist of Primary Data: Primbon Jawa Books, interviews with local community leaders, and the people involved, as well as Secondary Data sourced from books and scientific works. The conclusion from the conclusion is that the weton calculation that occurred in Balong Besuk Village, Diwek District, Jombang Regency is still being carried out. The factors that influence one of the most prominent is to maintain the legacy of the ancestors or ancestors. From the phenomena that occur. Giving rise to pros and cons, more or less there are people who practice and some do not. From the results of the research above, the researcher concluded that the calculation of weton in marriage from an Islamic law perspective is permissible if it does not conflict with the Qur'an and Sunnah and prioritizes the benefit of the community as well as tolerance in behavior.